Respon Tulang Femur Tikus Osteoporosis yang Mengkonsumsi Calcitriol - Hartiningsih Hartiningsih; Devita Anggraeni (Jurnal Sain Veteriner, 2018)
Calcitriol supplementation in ovariectomized rats decreased bone resorption and increased bone formation, however, it depend on dose. The objective of the research was to study the response of femur bone in osteoporosis rats consuming calcitriol. Thirty female Wistar rats at 8 weeks of age were randomly divided into six groups (sham operated rats as normal control rats/group N and NK, ovariectomized control rats/group Ov and OvK, ovariectomized rats/group OvDand OvE) of five each. All rats were fed standard diet for 8 weeks. At 16 weeks  of age, group N and Ov  were euthanized, the right femur were taken for histopathological  examination. Group NK and OvK were fed a standard diet, group OvD was fed a standard diet +40ng calcitriol;  and group OvE was fed a standard diet+25µg ethynil ethyl estradiol. Treatments were done for six weeks. At the end of study, blood samples were taken from plexus orbitalis medialis for estrogen analysis. All rats were euthanized using ketamine10% and xylazine 2%. Right femur was taken for histopathological examination  using hematoxylin and eosin stain, and immunohistochemistry using monoclonal antibody anti TRAP5b which was detected with streptavidin-biotin.         The results showed that estradiol level of the rats in group OvD was not significantly different compared with the rats in OvK group, however, it was significanly lower compared to the rats in group OvE. Histopathologic figure of right distal femur metaphysis in group OvD was shown lesser adipocyte in the bone marrow and more trabecular bone speculum compared to group  OvK, however, there was more adipocyte in the bone marrow and lesser trabecular bone speculum compared to group OvE. Immunohistochemistry of distal femur metaphysis in group OvD and OvE were revealed tartrate resistant alkaline phosphatase 5b (TRAP5b) expression in trabecular bone, which was located in bone marrow space and trabecular speculum surface as well. Based on the results, it can be concluded that calcitriol 40ng/day supplementation in osteoporosis rats for 6 weeks decreased bone resorption and increased bone formation distal femur metaphysis.